Preferential Incorporation of G Opposite Template T by the Low-Fidelity Human DNA Polymerase ι - Zhang, Yanbin (American Society for Microbiology, 2000)
DNA polymerase activity is essential for replication, recombination, repair, and mutagenesis. All DNA polymerases studied so far from any biological source synthesize DNA by the Watson-Crick base-pairing rule, incorporating A, G, C, and T opposite the templates T, C, G, and A, respectively. Non-Watson-Crick base pairs would lead to mutations. In this report, we describe the ninth human DNA polymerase, Polι, encoded by the RAD30B gene. We show that human Polι violates the Watson-Crick base-pairing rule opposite template T. During base selection, human Polι preferred T-G base pairing, leading to G incorporation opposite template T. The resulting T-G base pair was less efficiently extended by human Polι compared to the Watson-Crick base pairs. Consequently, DNA synthesis frequently aborted opposite template T, a property we designated the T stop. This T stop restricted human Polι to a very short stretch of DNA synthesis. Furthermore, kinetic analyses show that human Polι copies template C with extraordinarily low fidelity, misincorporating T, A, and C with unprecedented frequencies of 1/9, 1/10, and 1/11, respectively. Human Polι incorporated one nucleotide opposite a template abasic site more efficiently than opposite a template T, suggesting a role for human Polι in DNA lesion bypass. The unique features of preferential G incorporation opposite template T and T stop suggest that DNA Polι may additionally play a specialized function in human biology.